2017
DOI: 10.1371/journal.pone.0187034
|View full text |Cite
|
Sign up to set email alerts
|

Biological substantiation of antipsychotic-associated pneumonia: Systematic literature review and computational analyses

Abstract: IntroductionAntipsychotic (AP) safety has been widely investigated. However, mechanisms underlying AP-associated pneumonia are not well-defined.AimThe aim of this study was to investigate the known mechanisms of AP-associated pneumonia through a systematic literature review, confirm these mechanisms using an independent data source on drug targets and attempt to identify novel AP drug targets potentially linked to pneumonia.MethodsA search was conducted in Medline and Web of Science to identify studies explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
(113 reference statements)
0
13
1
1
Order By: Relevance
“…Data from randomized trials including mostly second-generation antipsychotics showed a higher risk of infections [ 78 ] (Table 1 ). Apart from immunity abnormalities [ 82 ], multiple mechanisms may contribute, including reduced clearance of the airways (related to central sedation and inhibition of cough), impaired chest movements and swallowing due to extrapyramidal symptoms, and sialorrea [ 51 ]. This risk might be particularly relevant for clozapine [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data from randomized trials including mostly second-generation antipsychotics showed a higher risk of infections [ 78 ] (Table 1 ). Apart from immunity abnormalities [ 82 ], multiple mechanisms may contribute, including reduced clearance of the airways (related to central sedation and inhibition of cough), impaired chest movements and swallowing due to extrapyramidal symptoms, and sialorrea [ 51 ]. This risk might be particularly relevant for clozapine [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is largely recognised with haloperidol presumably reflecting its potency as a dopamine D2 antagonist (Haddad and Dursun, 2008). Sultana et al (2017) used a systematic literature review with computational analyses to investigate possible pharmacological mechanisms to explain antipsychotic-associated pneumonia. Thirty studies included in the review suggested potential mechanisms with the most frequent involving effects on cholinergic, dopaminergic or histaminergic receptors.…”
Section: Potential Pharmacological Mechanismsmentioning
confidence: 99%
“…Les auteurs incitent ainsi à la vigilance chez les patients commenç ant des antipsychotiques et particulièrement chez ceux présentant des facteurs de risque de pneumonie, avec notamment : âge avancé, tabagisme, dysphagie, maladie respiratoire chronique ou cérébrovasculaire [32]. L'origine de cet impact délétère des antipsychotiques demeure très mal connue et si les théorisations autour de l'implication des systèmes cholinergique, histaminergique, sérotoninergique et dopaminergique sont formulées dans la littérature, il existe un biais d'interprétation mettant en exergue les études sur ce qui est « déjà connu » au détriment des pistes alternatives [33] ; cette revue suggère également l'implication de deux nouvelles cibles réceptologiques pouvant être associées à la pneumonie : le récepteur du thromboxane A2 et celui du facteur d'activation plaquettaire. Des données très récentes confirment ces éléments, en objectivant que chez les patients de 65 ans ou plus, hospitalisés pour pneumonie, une association est retrouvée entre l'utilisation d'antipsychotiques de seconde génération et une mortalité accrue, particulièrement chez ceux souffrant antérieurement de troubles psychiques ou cardiaques [34].…”
Section: Pneumonieunclassified